Analisis Optimasi Produksi Menu Paket D'roasting Menggunakan Metode Linear Programming (Studi Kasus : D'roasting Jamaksari) - Anisa Safira; Najwah Khairani; Siti Faujiah; Wiwi Susilawati; Bambang Hermawan (Universitas Labuhanbatu, 2026)
This study aims to analyze and optimize the production of menu packages at D’Roasting Jamaksari Restaurant using Linear Programming (LP) with the simplex method. The main problem faced by the restaurant is the limitation of production resources, particularly raw materials such as chicken, rice, and spices, which requires efficient production planning to maximize profit. This research employs a quantitative approach with a case study method. Primary data were obtained through direct observation and interviews with the management of D’Roasting, while secondary data were collected from internal documents and relevant scientific literature. The Linear Programming model consists of three decision variables: the daily production quantity of Nasi Putih Ayam (X₁), Nasi Kabsah Ayam (X₂), and the whole chicken package (X₃). The objective function is to maximize total profit, expressed as Z = 3,150X₁ + 4,050X₂ + 8,850X₃, subject to constraints on the availability of rice, chicken, and spices. The model was solved manually using the simplex method. The results indicate that the optimal production combination consists of 30 portions of Nasi Putih Ayam, 70 portions of Nasi Kabsah Ayam, and 30 whole chicken packages, generating a maximum daily profit of Rp643,500. This optimal solution satisfies all existing resource constraints. The implementation of Linear Programming proves effective in improving resource utilization efficiency, reducing waste, and supporting data-driven production decision-making. Therefore, this method can serve as a strategic tool to enhance operational efficiency and profitability at D’Roasting Jamaksari.